2019
DOI: 10.1002/cam4.2397
|View full text |Cite
|
Sign up to set email alerts
|

Colitis after checkpoint blockade: A retrospective cohort study of melanoma patients requiring admission for symptom control

Abstract: Background Immune checkpoint inhibitors (CPIs) have revolutionized oncologic therapy but can lead to immune‐related adverse events (irAEs). Corticosteroids are first‐line treatment with escalation to biologic immunosuppression in refractory cases. CPI‐related gastroenterocolitis (GEC) affects 20%‐50% of patients receiving CPIs and can carry significant morbidity and mortality. Severe CPI‐related GEC is not well‐described. We present the clinical characterization of all CPI‐related GEC requiring ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…Our results may therefore be biased toward more severe cases, as mild cases of irAEs are usually treated by dermatologists themselves. This might explain the reported severity of symptoms, high CTCAE grades, and the prevalence of complications, as a comparable recent study detected a need for surgery in 3/60 patients (vs. 2/33 patients in our study) [26]. Furthermore, it also explains why such a high number of 22 patients (67%) presented with a steroid-refractory disease course needed additional treatment with infliximab or even surgery.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our results may therefore be biased toward more severe cases, as mild cases of irAEs are usually treated by dermatologists themselves. This might explain the reported severity of symptoms, high CTCAE grades, and the prevalence of complications, as a comparable recent study detected a need for surgery in 3/60 patients (vs. 2/33 patients in our study) [26]. Furthermore, it also explains why such a high number of 22 patients (67%) presented with a steroid-refractory disease course needed additional treatment with infliximab or even surgery.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, it also explains why such a high number of 22 patients (67%) presented with a steroid-refractory disease course needed additional treatment with infliximab or even surgery. And it might also explain why the majority of patients had cancer progression despite severe colitis, which is in contrast to an earlier study investigating the disease course in patients with checkpoint inhibitor-induced colitis [26].…”
Section: Discussionmentioning
confidence: 74%
“…Thirty‐three studies reported outcomes on 1104 checkpoint inhibitor‐induced enterocolitis patients treated with corticosteroids. Just over half of data were contributed by 6 studies; Abu‐Sbeih et al 9 (n = 141), Wang et al, 2019 23 (n = 109), Nahar et al, 2019 24 (n = 106) Foppen et al 10 (n = 92), Spain et al 25 (n = 72) and Hughes et al(II), 2019 28 (n = 57). Reporting of the corticosteroid dose and regimen used was inconsistent and described in 20 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies incorporated a range of regimens including prednisolone (14 studies), hydrocortisone (3 studies), methylprednisolone (6 studies) and budesonide (5 studies). Three of the 6 largest aforementioned studies provide a more detailed description of the corticosteroid regimen employed, with Hughes et al(II) 28 reporting that 87.5% of patients received at least 1 mg/kg prednisone or equivalent; Foppen et al 10 describing budesonide use in 12 episodes and “high dose corticosteroids” in 92 episodes (32 episodes at a dose of <1 mg/kg, 57 at 1 mg/kg and 3 at >1 mg/kg) and Wang et al 23 reporting that anti‐PD‐1 monotherapy and combination regimen treated patients received a median of 1.0 and 1.5 mg/kg prednisone equivalent respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation